OP20 BLOOD SERUM AND CSF ANALYTES SHOW POTENTIAL FOR USE AS A DIAGNOSTIC BIOMARKER FOR LOW AND HIGH GRADE GLIOMA - Abel, Peter (Oxford University Press, 2014)
INTRODUCTION: There is a need for a biomarker with high sensitivity and specificity to aid glioma diagnosis. Current methods of diagnosis are invasive with the diagnostic test requiring hospitalisation. A rapid diagnostic based upon blood serum and CSF samples would allow for a relatively non-invasive test and open up the possibility of screening for glioma METHOD: Serum from 110 high grade and 44 low grade glioma patients, were analysed along with 33 control sera from non-cancerous patients. CSF was also analysed from 8 high grade glioma patients taken with lumbar puncture. The analysis was performed using a luminex immunoassay measuring 36 cancer-associated analytes simultaneously. RESULTS: There were significant differences in several analytes between sera and CSF of glioma patients of low and high grade and non-cancerous control patients. These were Angiopoietin, Follistatin, FGF, G-CSF, sHER2neu, HGF, sIL-6R, Leptin, PDGF-BB, PECAM-1, Prolactin and sVEGFR-1. CSF level differences confirmed and correlated with serum level differences in the majority of cases. CONCLUSION: These results suggest that specific protein levels in different media can be used to detect and confirm a glioma diagnosis as well as to distinguish between low and high grade gliomas. There was an interesting up-regulation of several receptor analytes that may have masked the presence of their associated ligand indicating that a masking effect may be taking place for certain potential biomarkers.